The direction and intensity of China's monetary policy conduct: A dynamic factor modelling approach - Michael Funke; Andrew Tsang (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
The recent upgrade of the People's Bank of China's monetary policy framework establishes a corridor system of interest rates. As the revamped policy arrangement now features a multiple-instrument mix of liquidity tools and pricing signals, we employ a dynamic factor modelling approach to derive an indicator of China's monetary policy stance. The approach is based on the notion that comovements in several monetary policy instruments have a common element that can be captured by a single underlying, unobserved component. To clarify and interpret the derived index, we employ a baseline DSGE model that can be solved analytically and allows tracing of the expansionary and contractionary on-and-off phases of Chinese monetary policy.
URN:NBN:fi:bof-201904251161
Keywords: C54; E52; E58; E61; E32; 330; China; monetary policy stance; dynamic factor model; DSGE model